Out of the shadow of Hendrick de Keyser (Bulletin KNOB, 2016)
Gerrit Lambertsen van Cuilenborch began his career in the studio of Hendrick de Keyser. Later he worked for the Danish king and as sculptor in Kampen and municipal building supervisor in Zwolle. The early classicism of Van Cuilenborch’s buildings in those two towns was quite obviously influenced by his teacher, Hendrick de Keyser. As with other architects, during the course of his career the superimposed rows of pilasters evolved into a colossal order of pilasters. The ionic capital of no. 14 Melkmarkt in Zwolle is planar, as was usual with Serlio and Hendrick de Keyser, whereas Vingboons and other contemporaries favoured the diagonal variant proposed by Scamozzi. Lions’ heads proved to be a useful decorative detail for making a distinction or attribution. Although an iconographic interpretation is as yet lacking, one encounters two different types of lions: stern or affable. Another element that changed over time is the oeil-de-boeuf window, but I have not pursued that in detail. Nor have I investigated the classical treatises or iconological sources that Van Cuilenborch may have consulted, as was done for Hendrik de Keyser’s Medusa in a recent erudite article in this journal.Although this article affords only a small glimpse of the life and work of the sculptor Gerrit Lambertsen van Cuilenborch and his studio, and although the attribu Aantion is far from absolutely certain, Van Cuilenborch does now have a recognizable, independent place in history. Van Cuilenborch used sample prints for his facade tablets. He also drew inspiration from models and studied Van Mander’s Schilder-Boeck, which referred to Amsterdam painters he would have known personally, such as Salomon de Bray and Pieter Isaacsz who had worked with him in Denmark for Christian IV. The high quality of his sculpture work in Amsterdam and Denmark is still discernible in various facade tablets and in the carved heads at no. 9 Broederweg in Kampen. With the exception of no. 100 Buiten Nieuwstraat in Kampen, the architectural quality of the facades he built in Kampen and Zwolle is inferior to those built previously under the auspices of Hendrick de Keyser. Van Cuilenborch was first and foremost a master sculptor, only secondarily a mason and, in common with most Dutch municipal building supervisors, no architect at all. With the assistance of other disciplines, such as carpenters and surveyors, he created new market squares in Kampen and Zwolle on the site of a former monastery. In Kampen the buildings were of a mainly representive character, while those around the square in Zwolle were more in the nature of what we would nowadays call property development.